Establishment and validation of a bad outcomes prediction model based on EEG and clinical parameters in prolonged disorder of consciousness - Liu, Wanqing; Guo, Yongkun; Xie, Jingwei; Wu, Yanzhi; Zhao, Dexiao; Xing, Zhe; Fu, Xudong; Zhou, Shaolong; Zhang, Hengwei; Wang, Xinjun (Frontiers in Human Neuroscience, 2024)
Objective: This study aimed to explore the electroencephalogram (EEG) indicators and clinical factors that may lead to poor prognosis in patients with prolonged disorder of consciousness (pDOC), and establish and verify a clinical predictive model based on these factors. Methods: This study included 134 patients suffering from prolonged disorder of consciousness enrolled in our department of neurosurgery. We collected the data of sex, age, etiology, coma recovery scales (CRS-R) score, complications, blood routine, liver function, coagulation and other laboratory tests, resting EEG data and follow-up after discharge.These patients were divided into two groups: training set (n=107) and verification set (n=27).These patients were divided into a training set of 107 and a validation set of 27 for this study.Univariate and multivariate regression analysis were used to determine the factors affecting the poor prognosis of pDOC and to establish nomogram model.We use the receiver operating characteristic (ROC) and calibration curves to quantitatively test the effectiveness of the training set and the verification set.In order to further verify the clinical practical value of the model, we use decision curve analysis (DCA) to evaluate the model.The results from univariate and multivariate logistic regression analyses suggested that an increased frequency of occurrence microstate A,reduced CRS-R scores at the time of admission, the presence of episodes associated with paroxysmal sympathetic hyperactivity (PSH), and decreased fibrinogen levels all function as independent prognostic factors. These factors were used to construct the nomogram.The training and verification sets had areas under the curve of 0.854 and 0.920, respectively. Calibration curves and DCA demonstrated good model performance and significant clinical benefits in both sets.This study is based on the use of clinically available and low-cost clinical indicators combined with EEG to construct a highly applicable and accurate model for predicting the adverse prognosis of patients with prolonged disorder of consciousness. It provides an objective and reliable tool for clinicians to evaluate the prognosis of prolonged disorder of consciousness, and helps clinicians to provide personalized clinical care and decision-making for patients with prolonged disorder of consciousness and their families.